Hfe is highly expressed in liver sinusoidal endothelial cells but is not needed to maintain systemic iron homeostasis in vivo - Colucci, Silvia; Müdder, Katja; Muckenthaler, Martina; Altamura, Sandro (HemaSphere, 2022)
An abstract is unavailable.
Gesehen am 12.01.2022